2019
DOI: 10.17135/jdhs.2019.19.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Depression, Oral Dryness, and Oral Health-Related Quality of Life among Elderly in Korea

Abstract: Background: This study aimed to analyze correlations between depression, cognitive function, oral health state, ability to perform activities of daily living, oral dryness symptoms, and oral health-related quality of life, and determine factors influencing the latter. Methods: This was a cross-sectional study based on questionnaires completed by 260 participants with suspected dementia, residing in South Korea. Psychiatrists, psychiatric nurses, and dental hygienists visited clinics in the participating region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
2
2
0
Order By: Relevance
“…This con rms the ndings of So-Jung et al .,201932 and Rozas et al .,202033 who reported a signi cant increase in BOHSE score of the institutionalized elders.With the exception of lymph node, lips and salivary problems, the present study showed no statistically signi cant in uence of gender on oral health problems .This result is in accordance with I˙lhan et al,201434 and Motallebnejad et al,201535 who reported that there is no signi cant difference between males and females in relation to their oral health status .The result also come in line with Arya et al,2020 36 and Moussa et al, 202037 who found that Poor oral health status was common among both sexes equally .On the contrary, the results of the present study disagree with studies done byHopcraft et al,2012 38,39 and Janssens et al,201740,41 who reported that the male residents were associated with a higher proportion of dental/periodontal problems. While.…”
supporting
confidence: 90%
“…This con rms the ndings of So-Jung et al .,201932 and Rozas et al .,202033 who reported a signi cant increase in BOHSE score of the institutionalized elders.With the exception of lymph node, lips and salivary problems, the present study showed no statistically signi cant in uence of gender on oral health problems .This result is in accordance with I˙lhan et al,201434 and Motallebnejad et al,201535 who reported that there is no signi cant difference between males and females in relation to their oral health status .The result also come in line with Arya et al,2020 36 and Moussa et al, 202037 who found that Poor oral health status was common among both sexes equally .On the contrary, the results of the present study disagree with studies done byHopcraft et al,2012 38,39 and Janssens et al,201740,41 who reported that the male residents were associated with a higher proportion of dental/periodontal problems. While.…”
supporting
confidence: 90%
“…These different ndings may be attributed to different sample size and mean age of the participants 24. This con rms the ndings of So-Jung et al .,201932 and Rozas et al .,202033 who reported a signi cant increase in BOHSE score of the institutionalized elders.With the exception of lymph node, lips and salivary problems, the present study showed no statistically signi cant in uence of gender on oral health problems .This result is in accordance with I˙lhan et al,201434 and Motallebnejad et al,201535 who reported that there is no signi cant difference between males and females in relation to their oral health status .The result also come in line with Arya et al,2020 36 and Moussa et al, 202037 who found that Poor oral health status was common among both sexes equally .On the contrary, the results of the present study disagree with studies done byHopcraft et al,2012 38,39 and Janssens et al,201740,41 who reported that the male residents were associated with a higher proportion of dental/periodontal problems. While.…”
supporting
confidence: 77%
“…Although this was a cross-sectional study, the Pearson correlation coefficient of the correlation with depression ( r = −0.560, p < 0.001) revealed a highly statistically significant outcome. Furthermore, another cross-sectional study involving participants with suspected dementia in Korea found that oral dryness and depression among older adults influenced oral health-related quality of life ( 10 ). A cross-sectional study using longitudinal data conducted in Germany by Hassel et al reported that oral health-related quality of life was significantly linked to wellbeing and depression in later life, assuming that subjective health could mediate this relationship ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, South Korea (hereafter, Korea) reported that older individuals with poor oral health are more likely to experience depressive episodes ( 9 ). A cross-sectional study by Mun et al emphasized the impact of depression and oral dryness on oral health-related quality of life ( 10 ). Globally, depression is a major public health concern and a leading cause of adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%